PENGARUH LATIHAN BOOMERANG RUN DAN LATIHAN SQUAT THRUST TERHADAP PENINGKATAN KELINCAHAN DRIBBLING BOLA - Zulfikar, Zulfikar; Syahruddin, Syahruddin (STOK BINA GUNA MEDAN, 2017)
This research aims to know the influence of exercise to increased agility run boomerang dribbling the ball, know squat thrust exercise influence towards increasing agility dribbling the ball, and want to know the difference of exercise bomerang run and squat thrust exercise against the increased agility of dribbling the ball. This type of research is a field experiment with independent variables, namely: exercise boomerang run (X1) and practice the squat thrust (X2), whereas the dependent are agility of dribbling the ball. The Club's Players in the research sample of Persisam Sampulungan Takalar as many as 40 people.  Each group, the frequency of exercise 3 times a week, the old exercise every 120 minutes of meetings with the number of meetings of each group of 18 times.  Analysis of data to test the hypothesis by using test-t significant extent α 0.10. The results showed that the practice of boomerang run influential significantly to increased agility ball, dribbling exercises squat thrust effect significantly to increased agility dribbling the ball, and exercise boomerang run better influence towards increasing agility dribbling the ball in the game of football than the squat thrust exercises.